Application of Pediococcus acidilactici BK01 Microencapsulated Starter on Nutritional and Organoleptic Value of Sweet Potato Flour (Ipomoea batatas L.) Fermented Milk - Supadil, Doni; Melia, Sri; Juliyarsi, Indri (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
Probiotics are live microorganisms that benefit to the body's health. One of which is Pediococcus acidilactici BK01, which is used as a microencapsulated starter in the manufacture of fermented milk.  This study aimed to determine the effect of adding several types of sweet potato flour (Ipomoea batatas L.) on the nutritional and organoleptic values of fermented milk. The research method used is an experimental method using a Randomized Group Design. The treatments were the addition of several types of sweet potato flour (Factor A): A1 (white sweet potato), A2 (purple sweet potato), C1 (yellow sweet potato), and the percentage of sweet potato addition (Factor B): B1 (0%), B2 (3%), B3 (6%). The results showed that the addition of sweet potato flour at different percentages had an effect (p < 0.05) on moisture content, protein content, fat content, and sensory value.  The conclusion of this study is that fermented milk with the addition of 6% purple sweet potato (A2B3) is a treatment that can be accepted by organoleptic panelists with 84.27% moisture content, 5.67% protein content, 1.59% fat content. For the future, the results of this study are expected that fermented milk with the addition of sweet potato can increase nutritional value and be used as a functional food that is beneficial for health.